THE IMPORTANCE OF FASTING IN CELL REGENERATION: A SCIENTIFIC AND ISLAMIC PERSPECTIVE - Andik Isdianto; Nuruddin Al Indunissy; Novariza Fitrianti; Abdul Hamid Arif; Wahyudi Widada (PT. Jurnal Center Indonesia Publisher, 2025)
Fasting is a religious practice that not only holds spiritual significance in Islamic teachings but also contributes substantially to the body's physiological repair. This study aims to examine the relationship between Islamic fasting—particularly Ramadan and sunnah fasting—and cellular repair processes through biological mechanisms such as autophagy, cell regeneration, and mitochondrial function enhancement. Using an integrative literature review method, this study synthesized findings from scientific and Islamic sources retrieved from databases including PubMed, Scopus, ScienceDirect, and Google Scholar from 2015 to 2025. The findings reveal that fasting positively affects systemic inflammation reduction, improved insulin sensitivity, metabolic regulation, and the prevention of premature aging and degenerative diseases. Moreover, fasting strengthens psychological and spiritual dimensions, supporting mental health and enhancing emotional resilience. This synergy between biological and spiritual benefits highlights fasting as a holistic health strategy. The study affirms that Islamic values align with modern preventive health principles and offer a solid foundation for spiritually based health promotion. Further research is recommended to evaluate specific biomarkers related to fasting-induced cell regeneration.